2006
DOI: 10.1902/jop.2006.77.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Matrix Derivative and Coronal Flaps to Cover Marginal Tissue Recessions

Abstract: The coronally positioned flap alone or with EMD is an effective procedure to cover localized gingival recessions. The addition of EMD significantly improves the amount of root coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 44 publications
7
131
0
3
Order By: Relevance
“…The test sites demonstrated better root coverage (92.9% after 6 months) compared to the control sites (66.8% after 6 months) [132] . These results were recently corroborated by others [133] . In a controlled, clinical, split-mouth study involving 17 patients, the therapy of buccal Miller class II recessions with a coronally positioned flap and EMD (test group) or flap alone was compared to connective tissue graft (control) [134] .…”
Section: Controlled Clinical Studies In Recession Defectssupporting
confidence: 84%
“…The test sites demonstrated better root coverage (92.9% after 6 months) compared to the control sites (66.8% after 6 months) [132] . These results were recently corroborated by others [133] . In a controlled, clinical, split-mouth study involving 17 patients, the therapy of buccal Miller class II recessions with a coronally positioned flap and EMD (test group) or flap alone was compared to connective tissue graft (control) [134] .…”
Section: Controlled Clinical Studies In Recession Defectssupporting
confidence: 84%
“…These findings are within the range reported by Castellanos et al . (2006)[11] and Prato et al . (2000),[12] where they found 88.6% and 62.2% of root coverage in patients treated with EMD+CPF and CPF alone, respectively, after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies 6,7,20) involving more cases and longer follow-up periods also found no significant differences between CPF and CPF‫ם‬EMD. Meanwhile, several studies 3,5,18) have shown significantly better outcomes with CPF‫ם‬EMD than with CPF in terms of percentage of root coverage, keratinized gingival gain, and attachment gain, revealing substantial variability in the outcomes of long-term studies of CPF‫ם‬EMD.…”
Section: Discussionmentioning
confidence: 99%